Distinct epigenetic features of differentiation-regulated replication origins - Smith, Owen K.; Kim, RyanGuk; Fu, Haiqing; Martin, Melvenia M.; Lin, Chii Mei; Utani, Koichi; Zhang, Ya; Marks, Anna B.; Lalande, Marc; Chamberlain, Stormy; Libbrecht, Maxwell W.; Bouhassira, Eric E.; et al. (Epigenetics & chromatin, 2016)
Background Eukaryotic genome duplication starts at discrete sequences (replication origins) that coordinate cell cycle progression, ensure genomic stability and modulate gene expression. Origins share some sequence features, but their activity also responds to changes in transcription and cellular differentiation status. Results To identify chromatin states and histone modifications that locally mark replication origins, we profiled origin distributions in eight human cell lines representing embryonic and differentiated cell types. Consistent with a role of chromatin structure in determining origin activity, we found that cancer and non-cancer cells of similar lineages exhibited highly similar replication origin distributions. Surprisingly, our study revealed that DNase hypersensitivity, which often correlates with early replication at large-scale chromatin domains, did not emerge as a strong local determinant of origin activity. Instead, we found that two distinct sets of chromatin modifications exhibited strong local associations with two discrete groups of replication origins. The first origin group consisted of about 40,000 regions that actively initiated replication in all cell types and preferentially colocalized with unmethylated CpGs and with the euchromatin markers, H3K4me3 and H3K9Ac. The second group included origins that were consistently active in cells of a single type or lineage and preferentially colocalized with the heterochromatin marker, H3K9me3. Shared origins replicated throughout the S-phase of the cell cycle, whereas cell-type-specific origins preferentially replicated during late S-phase. Conclusions These observations are in line with the hypothesis that differentiation-associated changes in chromatin and gene expression affect the activation of specific replication origins.